Potential role of sirtuin 1 in Müller glial cells in mice choroidal neovascularization. - Tomoka Ishida; Takeshi Yoshida; Kosei Shinohara; Kejia Cao; Ken-Ichi Nakahama; Ikuo Morita; Kyoko Ohno-Matsui (PLoS ONE)
This study investigated the potential role of sirtuin 1 in Müller glial cells in choroidal neovascularization. In the in vitro study, primary Müller glial cells were cultured and treated with resveratrol, a sirtuin 1 activator. Glial fibrillary acidic protein expression and angiogenesis-related gene expression were examined using quantitative polymerase chain reaction and phagocytosis, as a marker of Müller glial cell function; in addition, a latex bead assay was used to analyze cell function. For the in vivo study, choroidal neovascularization was induced in C57BL/6 mice via laser photocoagulation, and resveratrol was administered intravitreally. Eyecup whole mounts were created to measure choroidal neovascularization volumes on day 7. Immunohistochemical analysis with anti-glial fibrillary acidic protein antibody was used to detect Müller glial cell activation in eyes with choroidal neovascularization on day 1, 3, 5, and 7 after laser surgery. Resveratrol significantly promoted glial fibrillary acidic protein, anti-angiogenic factor, pigment epithelium-derived factor, and thrombospondin-1 expression in the cells as well as the phagocytic activities. Treatment of the choroidal neovascularization model with resveratrol resulted in early activation of Müller glial cells near choroidal neovascularization sites. Resveratrol-activated cells but not the controls migrated to the top of choroidal neovascularization sites and into the lesions from day 3. Resveratrol reduced the choroidal neovascularization size relative to controls. In conclusion, sirtuin 1 activation in Müller glial cells suppressed the development of choroidal neovascularization, and therefore, might be a therapeutic option.